The psychological well-being practices from Islamic perspective in families during the COVID-19 pandemic - Mohd Adnan, Sarah Dina; Nik Dahalan, Nang Naemah; Abdul Kadir, Nor Adina; Md Nasir, Mariam Farhana; Jalani, Hamidah; Zur Raffar, Izzah Nur Aida (2023)
Research conducted on the effects of the COVID-19 pandemic on society has revealed the presence of social obstacles arising from the detrimental influence on individuals' emotional and psychological well-being. These adverse effects manifest in several forms, including symptoms of stress, tension, anxiety, concern, melancholy, and depression, alongside the enduring economic difficulties experienced by affected individuals. The proliferation of COVID-19 and the implementation of the Movement Control Order (MCO) have had a widespread impact, including on parents who express concerns regarding the mental and emotional welfare of their children amidst the MCO. Additionally, parents are experiencing heightened stress levels due to the responsibilities associated with facilitating home-based learning and teaching, commonly referred to as the PdPR. Hence, to safeguard the ongoing welfare and contentment of the family, it is imperative to implement remedial measures aimed at mitigating the crises and stress that have been identified among parents amidst the pandemic, with a specific focus on the educational challenges encountered by children in a home-based setting. Hence, the present study was undertaken with the aim of identifying the strategies implemented inside families to uphold psychological well-being during the pandemic, as well as evaluating the extent to which these practises are employed. The present investigation was conducted as a survey study. The study employed quantitative data gathering methods, specifically by distributing questionnaire forms to a purposively selected sample of 516 parents. The collected data was then analysed using descriptive statistics in SPSS, including measures such as minimum, frequency, and percentage. The findings indicated that a majority of participants consistently engage in prayer and place their trust in a higher power (mean = 3.61) as a means of achieving psychological well-being. Furthermore, within the context of the pandemic, it is possible to identify three distinct stages of well-being practises among families, namely the low, moderate, and high stages. This study is anticipated to be utilised by parents and Muslim families who are grappling with contemporary issues. Furthermore, it is planned to serve as an indication for relevant stakeholders to offer educational resources, assistance, and programmes aimed at fostering family harmony in Malaysia.